Stress and coping in adolescence: Are storms and tornados just a myth or reality? - Zotović Marija; Petrović Jelica; Majstorović Nebojša (Psihologija, 2012)
The study was aimed to address three research questions: (1) what are most common stressful events and how adolescents subjectively rate their severeness, (2) how adolescents cope with stress events, and (3) are there any differences in coping in relation to the intensity of stress events experienced by adolescents. The study was conducted on the sample of 1504 adolescents from Vojvodina, age from 15 to 21. Participants were asked to fill out a general demographic profile questionnaire, Stressful experience scale, and A-COPE coping inventory. The results indicated a set of most stressful events experienced by adolescents. Seeking support from friends and avoidant behaviour were the most frequent coping mechanisms reported by participants. It was also established that among adolescents with higher level of stress, emotion focused strategies were used more often than among adolescents that were exposed to less stressful events. The results were discussed within the framework of existing theories and previous empirical findings.